Investigação dos aspectos clínicos na incompatibilidade materno-fetal em recém-nascidos na cidade de Manaus AM - Ferreira, Elione dos Santos (2016)
Maternal-fetal incompatibility is the etiological basis of clinical features that occur with fetal hemolytic anemia and post-natal jaundice, injury still persists on the world stage, especially in developing countries, despite advances in the past decades relating to the identification of blood group antigens, improved prenatal care and the introduction of therapy using serum containing antibodies against the RhD antigen. Objective: To investigate the clinical aspects of maternal-fetal incompatibility in newborns. Methods: A descriptive study was conducted in 1.425 newborns in Manaus - AM, in the months from may to september 2015, about the maternal-fetal incompatibility, linking clinical data with the blood typing test ABO and RhD, search irregular antibodies (P.A.I.) and the direct antiglobulin test (D.A.T.). In the analysis of categorical data was analyzed using the chi-square test with Yates correction and Fisher's exact test and comparison of two quantitative variables was applied the Pearson correction coefficient. Results: We found a frequency of blood group O in 61.3% of mothers and 61.1% of newborns with a predominance of positive RhD in 94.6% of mothers and 96.4% of newborns. There was a statistical significance between maternal-fetal ABO incompatibility and the presence of jaundice in 26.3% of cases (p <0.0001). The result of P.A.I. Positive was 0.2% of all mothers, with anti-RhD antibody found the unique irregularly. Considering only the Rh incompatibility, the percentage of P.A.I. positive becomes 5.5%, however, only one case of Hemolytic Disease of Newborn (HDN) was diagnosed. The newborns ABO incompatible group of mothers with children A or B had jaundice in a higher proportion than others ABO incompatibility. Conclusion: Maternal-fetal ABO incompatibility, even with P.A.I. and D.A.T. negative, it was an important factor, impacting in the presence of high jaundice. Maternal-fetal incompatibility cases with ABO hemolytic conditions and presence of jaundice were detected, however, no specific diagnosis in the hospital routines. The anti-RhD accounted for 100% of the results P.A.I. positive in RhD negative mothers, which highlights the need for greater management skill with a view to preventing alloimmunization